2006
DOI: 10.1016/j.pbb.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol responses to mental stress, exercise, and meals following caffeine intake in men and women

Abstract: Caffeine elevates cortisol secretion, and caffeine is often consumed in conjunction with exercise or mental stress. The interactions of caffeine and stress on cortisol secretion have not been explored adequately in women. We measured cortisol levels at eight times on days when healthy men and women consumed caffeine (250 mg × 3) and underwent either mental stress or dynamic exercise protocols, followed by a midday meal, in a double blind, placebo-controlled, crossover design. Men and women had similar cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
93
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 35 publications
9
93
1
2
Order By: Relevance
“…"Caffeine acts as an important modulator of cardiovascular and central nervous system activity" (Lovallo et al, 2006). Our results of drinking a cup of coffee on salivary cortisol are somewhat consistent with literature which reports no effect of caffeine on salivary cortisol levels in the absence of stress (Lovallo et al, 2006).…”
Section: Effect Of Drinking a Cup Of Coffeesupporting
confidence: 88%
See 4 more Smart Citations
“…"Caffeine acts as an important modulator of cardiovascular and central nervous system activity" (Lovallo et al, 2006). Our results of drinking a cup of coffee on salivary cortisol are somewhat consistent with literature which reports no effect of caffeine on salivary cortisol levels in the absence of stress (Lovallo et al, 2006).…”
Section: Effect Of Drinking a Cup Of Coffeesupporting
confidence: 88%
“…Therefore these studies suggest that caffeine does not elevate cortisol levels in the absence of stress. (Lovallo et al,2006;Shepard et al, 2000) Another study by Slivka et al (2008) investigators found no effect of 1 week of 1x200mg doses of caffeine supplementation on serum cortisol and serum DHEA levels (Mackenzie et al, 2007).…”
Section: Coffee Intake Effects On Cortisol Dhea Amylase and Vipmentioning
confidence: 99%
See 3 more Smart Citations